The perfect storm: Politics, media and child welfare policy - Harrison, C.; Harries, M.; Liddiard, Mark (Australian College for Child and Family Protection Practitioners Inc., 2014)
This paper is the first of a series emerging from a study of the practice of policy creation when a child welfare event comes to the notice of the public as a scandal and engages the attention of politicians and the media. The daily newspaper, The West Australian reported extensively on the Coroner's finding into the death of an 11month old toddler, Wade Scale, known to the child protection department. Debate and policy responses in the West Australian Parliament during the period of four months in 2006 are used as a case study to explore and identify the policy proposals that emerge out of a politicized landscape. The aim was the development of a theoretical framework and practical strategies to enable the public to have a more nuanced understanding of this complex issue and develop more supportive practice models for vulnerable families. The analysis identified specific policies dominated by a discourse of blame and regulation.